Curtain Up on Creative Robotics in Theatrical Experiments - samani, Hooman; Lalioti, Vali; Serbanescu, Diana Alina; Chicau, Joana; Polydorou, Doros; Rodosthenous, George; Jochum, Elizabeth (My University, 2025)
This paper presents key insights and reflections from the Creative Robotics Theatre workshop. The workshop brought together an interdisciplinary group of researchers, artists, and enthusiasts to explore the evolving intersection of robotics, performance, and creative arts. Through a combination of theoretical discussions, hands-on activities, and structured improvisations, participants engaged with fundamental concepts in robotic theatre and examined emerging paradigms in human-robot interaction. Key themes explored included the roles of robots in theatrical settings, the potential for robots to evoke empathy and challenge societal norms, and the use of performance techniques to expand imaginaries around human-robot relationships. The workshop highlighted the unique potential of theatre as a medium for exploring and shaping public perceptions of robotics technology. By synthesising diverse perspectives from computer science, robotics, performance studies, and design, this paper contributes to the growing discourse on creative robotics theatre and offers new directions for future research and artistic exploration in this rapidly evolving field.
Keywords: Applied Theatre; Robotics; Social Robotics; Theatre in Education; Theatre and Performance Arts